4D dose calculation for pencil beam scanning proton therapy of pancreatic cancer using repeated 4DMRI datasets - Dolde, Kai; Naumann, Patrick; Dávid, Christian; Saito, Nami (Physics in medicine and biology, 2018)
4D magnetic resonance imaging (4DMRI) has a high potential for pancreatic cancer treatments using proton therapy, by providing time-resolved volumetric images with a high soft-tissue contrast without exposing the patient to any additional imaging dose. In this study, we aim to show the feasibility of 4D treatment planning for pencil beam scanning (PBS) proton therapy of pancreatic cancer, based on five repeated 4DMRI datasets and 4D dose calculations (4DDC) for one pancreatic cancer patient. To investigate the dosimetric impacts of organ motion, deformation vector fields were extracted from 4DMRI, which were then used to warp a static CT of the patient, so as to generate synthetic 4DCT (4DCT-MRI). CTV motion amplitudes <15 mm were observed for this patient. The results from 4DDC show pronounced interplay effects in the CTV with dose homogeneity d5/d95 and dose coverage v95 being 1.14 and 91%, respectively, after a single fraction of the treatment. An averaging effect was further observed when increasing the number of fractions. Motion effects can become less dominant and dose homogeneity d5/d95 = 1.03 and dose coverage v95 = within the CTV can be achieved after 28 fractions. The observed inter-fractional organ and tumor motion variations underline the importance of 4D imaging before and during PBS proton therapy.
Gesehen am 08.04.2019